Legal Certainty of Restitution for Victims of Human Trafficking Crimes - Maulana Hilal Adnan; Yuni Priskila Ginting (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2026)
Case Number 7834 K/Pid.Sus/2024 concerns a human trafficking offence in which the cassation ruling imposed custodial punishment and mandated restitution calculated by the Witness and Victim Protection Agency (LPSK). This research is motivated by the need to protect victims' rights through restitution, despite ongoing implementation issues. Focusing on the degree of legal certainty in the implementation of restitution, this study analyzes the relevant decision through a normative juridical lens. The methodology incorporates statutory, conceptual, and case-based approaches, all of which are applied to secondary data consisting of primary legal sources, secondary literature, and tertiary references. The results showed that legal certainty regarding restitution for victims of human trafficking still faces various obstacles in Law No. 21 of 2007, which does not clearly regulate how to calculate, determine, and enforce compensation payments. The Supreme Court's decision in this case fills a legal void in Law No. 21 of 2007 by emphasizing that restitution must be calculated accurately based on the actual losses suffered by the victim, and recognizing the LPSK's calculation as a valid basis for determining the amount of restitution. It was concluded that the Supreme Court ruling strengthens legal certainty by legitimizing the LPSK's assessment, thereby providing a more concrete mechanism for enforcing restitution. The findings are expected to generate recommendations for law enforcement authorities and LPSK on the significance of enforcing restitution as an integral component of restoring victims’ rights and achieving justice in human trafficking cases.